Plant sulfolipid. III. Role in adaptation - Kosyk, O.I.; Okanenko, A.A.; Taran, N.Yu. (Інститут молекулярної біології і генетики НАН України, 2009)
The quality and/or relative content of plant sulfoquinovosyl diacylglycerol (SQDG) change in response to a stress action. Various types of stress action induce two types of response – more general to the oxidative stress and specific – to a concrete stress factor. Besides, two types of reaction take place in photosynthesizing and non-photosynthesizing tissues. SQDG molecules take part in the adaptation reaction being cytochrome oxidase, CF1, F1, ATPase regulators, protectors and stabilizing agents for D1/D2 dimers and LHC II. This compound in non-photosynthesising tissues could be connected with negative charge domination required for lipoprotein complex stabilisation. SQDG quantitative changes and acyl composition shifts take place at both abiotic and biotic factors impact.